CEO duality and companies’ performance: a case of Malaysian Companies / Roshima Said…[et al.] - Said, Roshima; Omar, Ropidah; Awang, Norasmila; Yaacob, Zuraini; Ismail, Jurina (Research Management Institude, Universiti Teknologi MARA, 2005)
The proponents of the agency theory and the stewardship theory had a different view on what constitute a good governance practice in the public firms. The agency theory believed that the separation of chief executive officer (CEO) and board chair roles is necessary to reduce the managers’ opportunistic behaviors which could reduce the shareholders’ wealth. In contrast, the stewardship theory believed that CEO duality promotes flexibility and reduces conflict between the board of directors and management, which in turn lead them to perform effectively. The objective of this study is to examine the relationship between CEO duality and companies’ performance. The researchers want to investigate whether the performance of the company is determined by their duality or independent leadership status. The findings of the study show that the independent leadership companies showed a better performance in term of the proportion of return on asset to leverage (ROE) and profit after tax and interest to sales (profit margin) as compared to the CEO duality companies. The difference is however, not statistically significant. Therefore, we can conclude that the separation of the roles of CEO and chairperson does not necessarily contribute to a better performance and that the duality issue is not a contributing factor in determining the performance of a company.